Modeling of bar anchorage in concrete - Y. V. Krasnoschekov (Вестник СибАДИ, 2017)
The article dwells on the results of computer modeling of pilot samples designed to testing for pulling out deformed reinforcement from concrete. The author analyzes the stress-strain state of finite elements of certain models, determines the areas of the probable cracks formation at elastic deformation of materials. The author discovers the character of concrete destruction on the different theories of durability. The particular attention is paid to identifying conditions of dangerous phenomenon of splitting concrete in the area of bar anchorage.